Results from a stakeholder survey on bioeconomy monitoring and perceptions on bioeconomy in Germany - Walther Zeug; Forrest Rafael Kluson; Nora Mittelstädt; Alberto Bezama; Daniela Thrän (Helmholtz-Zentrum für Umweltforschung (UFZ), 2021)
Our current economic systems are transgressing planetary boundaries globally and yet societal needs are not sufficiently and equally fulfilled. Fostering the bioeconomy as an economy based on renewable resources can be a transformation towards a sustainable future, to fulfill societal needs within planetary boundaries. However, sustainability is not intrinsic to the bioeconomy and consequently advanced and comprehensive monitoring systems on a national scale are needed. In the systemic modeling and monitoring of the German bioeconomy (SYMOBIO) a comprehensive national monitoring framework in the context of global dynamics was developed, and a first pilot report of monitoring results was published and presented to the public in June 2020. Stakeholder participation plays a role in informing monitoring from the beginning. Consequently, in this study we aim at evaluating the pilot report and monitoring as well as the general perception of the bioeconomy by an open survey. We collected approximately 100 responses, mainly from the stakeholder group "science". Most stakeholders are moderately satisfied with the monitoring and reporting. However, social aspects of the bioeconomy like hunger, poverty and inequalities are considered to be underrepresented, and the socio-economic perspective is viewed as too narrow. Future monitoring efforts should be oriented more on international agreed frameworks like the SDGs and be comparable to other monitoring systems and levels. Regarding general perceptions of the bioeconomy, a majority of stakeholders have a vision of a socio-ecological transformation, in contrast to German and European strategies which are seen as business-as-usual capitalism using additional renewable resources. Even though most stakeholders see the current development of bioeconomy critically, they consider the future development as open and encourage a sustainable bioeconomy that creates sustainable consumption and production patterns, global responsibility and compliance with planetary boundaries, as well as economic and ecological justice and participation shaping the overall economy. Our analysis underpins previous perspectives from stakeholder workshops and is embedded in increasingly polarizing societal mentalities of transformations.
Keywords: 330; bioeconomy; sustainability; monitoring; stakeholder participation